Current research trends on smart ports in the last decade: A theoretical application for supply chain management (LACCEI, 2024)
The research identifies and analyzes the main academic trends developed on the use of smart ports in the last decade. The PRISMA bibliographic review of literature from journals indexed in Scopus and others anchored to the SJR is used as a methodology. Sustainability, information technologies and infrastructure on the use of smart ports for supply chain management were taken as variables. As a main result, it was identified that the three variables provide added value, competitiveness, and efficiency in the management of the microgrid system for the reinvention of the maritime supply chain, transforming it into a solid connection in the fourth industrial revolution.